Toxicity evaluation of synthetic waters based on Br-Cl-I-THMs formation during the chlorine/ammonia process - Allard, Sebastian; Tan, J.; Charrois, Jeffrey; Joll, C.; Heitz, A.; Von Gunten, Urs (AMER CHEMICAL SOC, 2014)
Monochloramine (NH2Cl) is commonly used as an alternative to chlorine for disinfection because it is less reactive with the organic matrix, therefore forms less regulated DBPs and leads to a more stable residual. However, emerging DBPs such as I-DBPs which are more cytotoxic and genotoxic than the corresponding regulated Cl-Br-DBPs may be produced during chloramination. To mitigate the formation of I-DBPs, a common option is the application of the chlorine/ammonia process. The water is allowed to be in contact with chlorine to oxidise iodide to iodate, therefore mitigating the formation of I-DBPs. Then ammonia is added to form NH2Cl to control the formation of regulated DBPs. To better understand the mechanisms involved in the mitigation of I-DBPs during the chlorine/ammonia process, synthetic waters spiked with iodide and bromide at typical drinking water concentrations and different DOM extracts from the IHSS were subject to 3 disinfection scenarios: NH2Cl alone, pre-chlorination at different contact times followed by ammonia addition and HOCl alone. A theoretical toxicity evaluation was carried out based on the THMs formation and their relative toxicity equivalents to discriminate the 3 disinfection strategies studied. Results showed that the pre-chlorination time, the bromide concentration and the type and concentration of DOM are important parameters that control the formation of I-THMs and iodate. Regarding the cytotoxicity, the chlorine/ammonia process is not always favourable. For highly reactive DOM, the decrease in toxicity induced by the conversion of iodide to iodate during chlorination was compensated by the toxicity of regulated THMs.Conversely, for DOM with lower reactivity, the application of chlorine clearly reduced the formation of I-THMs while the toxicity of regulated THMs remained relatively low. In this case, because of the I-THMs mitigation, the application of chlorine led to a lower relative toxicity (based on THMs), as compared to the application of NH2Cl.